Mechanistic role of CD82 palmitoylation in augmenting antitumor drug sensitivity via apoptosis regulation - Li, Lanyan; Yu, Yaning; Chen, Sirui; Zhang, Yihuan; Zhang, Can; Yao, Xinyu; Xu, Hongli; Wu, Shihao; Gong, Xue; Han, Weiping; Zhang, Yu; Li, Ying (Frontiers in Oncology, 2025)
IntroductionCD82, a metastasis suppressor, is known to be palmitoylated, yet the functional significance of this modification in drug response remains unclear. This study investigates the role of CD82 palmitoylation in modulating chemosensitivity in triple-negative breast cancer (TNBC) cells.MethodsA palmitoylation-deficient CD82 mutant (C5A/C74A/C83A) was generated and expressed in MDA -MB-231 breast cancer cells. Protein palmitoylation was assessed via acyl-biotin exchange assay. Subcellular localization was analyzed by co-immunofluorescence with early endosome (EEA1) and vesicular (VPS4A) markers. Apoptosis was evaluated by measuring levels of apoptotic markers. The cytotoxic effect of the CD82 mutation in combination with gefitinib, doxorubicin, paclitaxel, and camptothecin was quantified using TUNEL and Annexin V/PI assays.ResultsThe CD82 palmitoylation-deficient mutant exhibited reduced palmitoylation and increased colocalization with EEA1 and VPS4A. This mutation triggered intrinsic apoptosis, as evidenced by elevated levels of Caspase-3, Cleaved-caspase-3, and Cytochrome C. Strikingly, it synergistically enhanced the cytotoxicity of both gefitinib and doxorubicin, significantly increasing apoptosis in treated cells.DiscussionOur findings reveal a novel role for CD82 palmitoylation in regulating drug-induced apoptosis. Disruption of palmitoylation potentiates chemotherapy-induced cell death, providing a molecular rationale for targeting CD82 palmitoylation as a combinatorial strategy to overcome therapeutic resistance in TNBC.